(untitled) (Research, Society and Development, 2019)
The Hydrographic Basin of Ribeirão Candidópolis is of great importance for Itabira (MG), supplying more than 55% of the urban population of this municipality. However, anthropic interventions in the region have promoted degradation in portions of this basin, interfering in the quality of the water used for supply and altering the hydrological cycle by modifying the infiltration and surface runoff stages. In this way, this work aimed at characterizing the morphometric parameters of this basin. For this purpose, a database was used for the use and occupation of the soil in the basin and the ArcGIS software for the determination of data referring to the area, perimeter, main talweg length, among others, necessary for the determination of the morphometric parameters represented by the circularity and roughness indexes, shape factor, drainage density and compactness coefficient. It was verified that due to its physical characteristics, the Hydrographic Basin of Ribeirão Candidópolis has a low drainage density and is not prone to flooding. In addition, it was noted that the predominance of pasture areas interferes with the infiltration of precipitation, resulting in high values of maximum runoff flow. In general, the importance of the preservation of native vegetation and the recovery of degraded areas in the basin are emphasized, aiming at maintaining the hydrological cycle and avoiding the contamination of surface waters.